Міокардіальні м’язові містки коронарних артерій: діагностика і лікування у практиці сімейного лікаря - Тихонова, Т.М.; Бичкова, О.Ю.; Бутова, Т.С.; Внукова, А.С. (ХМАПО, 2020)
The article presents data on prevalence, etiopathogenetic aspects, clinical manifestations, features of diagnosis and principles of treatment of myocardial muscle bridge. The attention of family doctors and pediatricians is drawn to the timely diagnosis of this congenital condition. The clinical case of diagnosed myocardial muscle bridge in a patient with atherosclerosis of the coronary arteries is presented.
Myocardial muscle coronary arteries: diagnosis and treatment in the practice of a family doctor
Keywords: coronary arteries; myocardial muscle bridge; diagnostics; treatment